Successful hemostasis in refractory alveolar hemorrhage using low-dose recombinant activated factor VII - John Selickman; Jacob Fiocchi; Hem Desai; Kathryn M. Pendleton (Respiratory Medicine Case Reports, 2022)
Diffuse alveolar hemorrhage (DAH) is a life-threatening condition requiring prompt recognition. Conventional therapy, even when initiated early, may not have an immediate effect, and in severe cases, bleeding can persist despite treatment. We report the case of a previously healthy 33-year-old male who developed DAH secondary to granulomatosis with polyangiitis, resulting in respiratory failure and the need for mechanical ventilation. High-dose corticosteroids, plasma exchange, and remission induction with cyclophosphamide failed to control bleeding, leading to severely impaired gas exchange. 20 mcg/kg of systemic recombinant activated Factor VII (rFVIIa), a dose lower than previously reported for management of DAH, resulted in hemostasis and improved oxygenation after only three doses. No complications were observed, and our patient was liberated from ventilatory support eight days later. In the setting of DAH with refractory bleeding, hemostasis may be achievable with a lower dose of rFVIIa than commonly used, potentially mitigating the risk of dose-dependent side effects.